On a Theorem of Ziv Ran concerning Abelian Varieties Which Are Product of Jacobians - Cristian Anghel; Nicolae Buruiana (Journal of Mathematics)
We give a new proof for a theorem of Ziv Ran which generalizes some results of Matsusaka and Hoyt. These results provide criteria for an Abelian variety to be a Jacobian or a product of Jacobians. The advantage of our method is that it works in arbitrary characteristic.